Relationship of molting trait and egg production on crossbred Peking and Alabio ducks - Triana Susanti; R.R Noor; P.S Hardjosworo; L.H Prasetyo (Jurnal Ilmu Ternak dan Veteriner, 2012)
Selection program through 6 months egg production record as criterion of selection can improve number of egg in a year. However the selected population has still showed molting which is influenced the cessation of egg production, so that its production has not optimal yet. The research has conducted to further learn about the relationship between molting and egg production. This study used 90 females AP ducks (the crossbred of Alabio ♂ and Peking ♀) and 90 females PA ducks (the crossbred of Peking ♂ and Alabio ♀). Observed variables were onset of molting, the length of molting periode and the egg production for 48 weeks. The collected data were analyzed by analysis of variance, correlation and regression. The results showed that based on the starting time of molting the ducks can be categorized into two group i.e (a) molting duck group and (b) non-molting duck group. There were 63 PA ducks characterized non-molting and 21 molting, and there were 42 non-molting and 45 molting in AP ducks. The egg production of these two groups was significantly different (P < 0.01). Since the molting was negatively correlated to the 48 weeks egg production (r = -0.896 for PA and -0.553 for AP), then this trait can be used as the selection criterion for egg production.The linear regression equation for PA of 48 weeks egg production = 80.7-0.369 molting duration, and for AP of 48 weeks egg production = 84 - 0.299 molting duration. Key Words: Molting, Egg Production, Duck